Too sensitive to create? The impact of the outbreak of the pandemic on the work of professional artists - Janiszewska-Szczepanik, Agnieszka (Kultura i twórczość w czasach zarazy: Doświadczenie pandemii a aktywność artystyczna z punktu widzenia twórcy i odbiorcy, 2021)
In the article I discuss the issue of dependence of the need to create on the need for safety according to selected theories of needs, and also I indicate possible reactions of artists to the situation of external threat. In the theoretical part, I refer, among others, to the theories of needs by Abraham Maslow, Tomasz Kocowski, Jan Szczepański and Kazimierz Obuchowski, in which creativity is frequently associated with the need for self-realisation. The concept of “high sensitivity” by Elaine Aron has also been presented as a factor that hinders an individual from freely realising their creativity, especially in the conditions of no a sense of stability. Subsequently, on the basis of interviews with artists, I analyse to what extent involvement in artistic activities requires a sense of safety of the creator and what is the impact of the so-called “artistic sensitivity” on maintaining activities in conditions of widespread anxiety and external difficulties (on the example of the pandemic). I distinguish three possible types of the artists’ responses to a safety threat, along with an explanation of their possible causes. The quoted excerpts from interviews with artists serve as an example of the artists’ reactions to the existing external situation.